Modeling of small radiation doses on the elastic characteristics of DNA - Kamlyuk, Андрей; Shirko, Алексей; Zhavoronkov, Илья (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The effect of small doses of radiation on human an example DNA molecule is considered. Proposed and studied the linear model of the DNA molecule in a viscous environment with the help of the Lagrange equations. The calculated values are obtained for the DNA molecule breaks by small doses of radiation. A comparison was made the theory with experiment. The results obtained can be used to predict the effects of small doses of radiation on the DNA molecule and the human body as a whole.